(untitled) (Fiep Bulletin - online, 2013)
The present study sought to verify the social representation on the lessons of Physical Education for pupils in 8th grade of elementary school in State College Marechal Rondon de Campo Mourao - Pastor was a qualitative research, which used a semi-structured, with roadmap not fixed as sampling and 18 students from 8th grades. We seek understanding in the speech of students, said by the unsaid and the representations they have on the lessons of Physical Education. Thus, we realize that the lessons of Physical Education are important to them, but the significance lies in another sphere in the sphere of pleasure, to do by doing, it has character of leisure-entertainment. In their speeches on the desired class show their desires to know and work with cooperative games, entertainment, dance, theater, karate, among others, and also theoretical fad practices, experiences foreground. Conceptualize the good teacher as well as one that charged the rules of the students, the meeting also allows us to infer that the teacher should be the model, the mirror to be followed by the students. With regard to gender representation by the great stress that fosters this is the prevalence of content based on sports activities in competition and force, which reinforces the concept of bias from strong man and woman frágil.Tópicos as physical development and welfare were mentioned in number smaller than the sport.